2019
DOI: 10.29219/fnr.v63.3601
|View full text |Cite
|
Sign up to set email alerts
|

Rhus verniciflua leaf extract suppresses obesity in high-fat diet-induced obese mice

Abstract: BackgroundObesity is a serious health problem in the world. We thought that the activity and safety of natural plants and/or foods are very important in the management of therapy for obesity. Rhus verniciflua (R. verniciflua) is also known as lacquer tree in Japan and Korea, and it is consumed as food ingredients and/or traditional herbal medicine. We prepared an extract from R. verniciflua leaves (Rv-PEM01-99) to develop a new functional food material and/or nutritional supplements.ObjectiveThis study evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The main component of the anti-inflammatory compound, Rv-PEM01-99, is quercetin derivative. 16,17 Quercetin is a flavonoid which has various functions such as antioxidant activity, anti-inflammatory action, amelioration of lipid metabolism and others. 15,20,21 Quercetin supplementation is effective for improvement of lipid metabolism in obese animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main component of the anti-inflammatory compound, Rv-PEM01-99, is quercetin derivative. 16,17 Quercetin is a flavonoid which has various functions such as antioxidant activity, anti-inflammatory action, amelioration of lipid metabolism and others. 15,20,21 Quercetin supplementation is effective for improvement of lipid metabolism in obese animals.…”
Section: Discussionmentioning
confidence: 99%
“…A long-term supplementation may be needed to show body weight reduction and antioxidant action as chronic effects as shown in mice. 17 It is reported that high concentrations of quercetin show side effects to inhibit cytochrome P450 isoforms 28 and metabolism of paclitaxel, an anticancer drug. 29 Whereas, Rv-PEM01-99, quercetin derivative, does not show such side effects, 16,17 therefore we can supply high concentrations of quercetin derivative to enhance its anti-oxidant and anti-inflammatory activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suruga et al [ 80 ] injected a Rhus verniciflua leaf extract to high-fat diet-induced obese mice to demonstrate its antiobesity effects. In mice injected with the extract, the rate of weight gain was reduced when compared with the control group mice.…”
Section: Acupuncture Herbs and Adipokinesmentioning
confidence: 99%
“…Toxicodendron vernicifluum Stokes (TVS) was found to contain a number of bioactive phytochemicals, including alkaloids, polyphenols and flavonoids [12]. Previous research has shown that TVS extract has antioxidant, anti-bacterial, anti-obesity, anti-proliferative, anti-inflammatory, and anti-tumor effects [12][13][14][15][16][17][18][19][20][21][22]. Despite the beneficial pharmacological effects of TVS, its use has been somewhat limited due to the presence of urushiol an allergenic substance, that is a mixture of several derivatives of catechol.…”
Section: Introductionmentioning
confidence: 99%